Comparison of student's satisfaction on school food service environment by the eating place and gender - Jung, Jisook (The Korean Nutrition Society and The Korean Society of Community Nutrition, 2009)
The purpose of this study was to compare student's satisfaction with school food service environment to improve the quality of middle school meal service. A survey was conducted of 680 students (boys 246, girls 433) from 6 middle schools providing school meals from October to November 2007. The questionnaires were directly distributed to the subjects for comparison of satisfaction of school meals depending on the eating place. As for the quantity of food, classroom group (3.40) expressed significantly higher satisfaction than cafeteria group (3.16, P < 0.01), but as for the satisfaction on hygiene, classroom group (2.76) showed significantly lower satisfaction than cafeteria group (3.03, P < 0.01). About the satisfaction of school meal environment, classroom group showed more satisfaction on distribution time, eating place, eating atmosphere (P < 0.001). The classroom group showed higher satisfaction than cafeteria group in cases of quantity, diversity of types of soup, dessert, and the cost of school meal. To improve eating place and hygiene of school meal, sufficient cafeteria space and pleasant environment is needed to be established.